Singing voice and Surface Electromyography: A comparative study of muscle activity in trained and non-trained singers - Puig Herreros, Clara; Rosell Clari, Vicent (Revista de Investigación en Logopedia, 2018)
In recent years, there has been an increase in the use of surface electromyography in speech therapy, which is evidenced in the growing number of publications in this area in scientific journals. This instrument can be objectively and accurately presented myoelectric activity in real time, non-invasive and perceived easy to apply. The aim of this work is to compare the myoelectric activity of the masseter, suprahyoid and sternomicleidomastoid muscles of singers with and without vocal training regulated through surface electromyography, during the performance of a phonetogram. The sample consisted of 12 sopranos with ages between 19 and 29 years, 6 with singing training and 6 without training. Prior to data collection, the acoustic analysis system was calibrated through a calibrator and a dosimeter. Samples were collected in a soundproof studio, with prior informed consent of the participants. The electrodes were fixed in each of the muscles, both right and left, and the protocol for recording myoelectric activity was carried out. Statistically significant differences were observed at the level of the sternocleidomastoid muscles, with their activity being greater in the training singers compared to the non-training ones. No significant differences were observed in the other muscles studied. It has been found that singers with training have greater activity at the level of sternocleidomastoid muscles compared to the non-training ones. Further research is needed with larger samples to arrive at more conclusive results.